Exploring the Key Factors in the Implementation of the GERMAS Policy: A Public Management Perspective Using the Mazmanian and Sabatier Framework - Maisarah, Ghina; Yusran, Rahmadani (Journal of Educational Management Research, 2025)
The implementation of the Healthy Living Community Movement (GERMAS) at the local level extends national health policies aimed at improving public health. This study examines the implementation of Regent Regulation No. 48 of 2019 on GERMAS in Pangkalan Koto Baru Subdistrict, utilizing the Mazmanian and Sabatier policy implementation model. A qualitative approach, including interviews, observations, and document analysis, was employed with policy implementers and community stakeholders. Findings reveal three key factors influencing implementation: (1) policy clarity and consistency, hindered by the lack of derivative regulations at local levels; (2) implementer capacity and commitment, limited by insufficient funding; and (3) social support, weakened by low public participation and ineffective health communication strategies. These results suggest that policy success depends on aligning institutional design, bureaucratic capacity, and community readiness. In management terms, effective policy execution requires strong leadership, efficient resource management, and active stakeholder engagement. Strengthening regulatory frameworks, ensuring sustainable funding, and adopting participatory communication strategies are critical for improving GERMAS implementation at the grassroots level. This study highlights the importance of management practices, including strategic planning, resource allocation, and community engagement, in enhancing the effectiveness of public health policies.